Market Society or Society of Marketness? An Analysis Based on the Controversy between Karl Polanyi and Douglass North–《Sociological Studies》2011年04期 - Yonghua, Liu (2011)
Karl Polanyi and Douglass North hold totally opposite views on the understanding of the industrial revolution.The former analyses the formation of market society within the framework of mutual benefit,reallocation and market analysis,while the latter is interested in the essential importance of transaction cost and institutional transition to the industrial revolution.This paper attempts to rediscover the implication of modern society and the sense of freedom which is closely related to it by illuminating these two scholars' understandings.
Sociology
Keywords: NORTH; Douglass; industrial revolution; market society

Backwash and Beyond: the Assumption of "Social Man" vs "Economic man": From Karl Polanyi to Mark Granovetter——The Latest Developments of the New Economic Sociology - Deshun, Zang (The Journal of Gansu Administration Institute, 2009)
As the hard core of western economic theory, the "economic man" assumption has been contradicted and challenged by the "social man" assumption since it formatted, which promotes economic theory to have adjusted its protective belt to promote the development of economics discipline. Polanyi's " embedded" theory, as the base of economic sociology which takes "social man" assumption as its hard core, is a subversive critique to "economic man" assumption. Based on "social man", New Economic Sociology (NES), established by Granovetter and others, regards men as "social men" firstly, and examines their social relations and institutions, and then analyzes the incentive mechanism of economic behavior. NES supplementally and even alternatively explains some theories proposed by economic models driven by traditional rational choice and utility. Thus, communion and dialogue has become inescapable to those subjects which are the same studying objects of the two disciplines.
Sociology
Keywords: economic man; embeddedness